2021
DOI: 10.1111/iju.14532
|View full text |Cite
|
Sign up to set email alerts
|

Comparative outcomes of flexible ureteroscopy and mini‐percutaneous nephrolithotomy for pediatric kidney stones larger than 2 cm

Abstract: To compare the outcomes of flexible ureteroscopy and mini-percutaneous nephrolithotomy for pediatric kidney stones larger than 2 cm and to show the learning curves for the two procedures. Methods: A prospectively managed database containing pediatric patients with kidney stones larger than 2 cm from June 2014 to October 2019 was analyzed. The primary outcomes were the efficacy and safety of flexible ureteroscopy and mini-percutaneous nephrolithotomy. Data on patient demographics, treatment details, stone-free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…They concluded that the RIRS success rate decreases markedly with stone size above 20 mm [ 24 ]. Also, Zhang et al reported that the SFR achieved by RIRS for stones larger than 2 cm was 79.7% and 80.9% after mini-PCNL [ 25 ]. However, Pelit et al found out that for pediatric stones the SFR of RIRS (75%) was less than the SFR of mini-PCNL (84.4%) [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that the RIRS success rate decreases markedly with stone size above 20 mm [ 24 ]. Also, Zhang et al reported that the SFR achieved by RIRS for stones larger than 2 cm was 79.7% and 80.9% after mini-PCNL [ 25 ]. However, Pelit et al found out that for pediatric stones the SFR of RIRS (75%) was less than the SFR of mini-PCNL (84.4%) [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has a high success rate with a less invasive procedure. 2,3 Suliman et al 11 employed FURS in pediatric stones with an SFR in the first session reaching 75% and a total SFR reaching 89%. While Chandramohan et al 5 employed FURS in preschool pediatric stones with an SFR reaching 76.3% for stones less than 20 mm.…”
Section: Discussionmentioning
confidence: 99%
“…The bleeding risk associated with PCNL has encouraged surgeons to use flexible ureteroscopy in children. 2,3 This research aims to evaluate the efficacy and safety of FURS in treating children in our center during the last 5 years.…”
Section: Introductionmentioning
confidence: 99%
“…ShuoTong lens can establish the working channel of the soft and hard lens, integrate gravel and stone removal, increase stone clearance rate, avoid stone escape, and achieve ideal clinical efficacy. Currently, the application of ShuoTong in the treatment of polycystic kidney disease complicated with kidney stones is rarely seen, and further research is still needed (14,15). The purpose of this study was to use UMP combined with ShuoTong ureteroscopy in the treatment of polycystic kidney stones and to explore the effects of different treatment methods on the stress response, inflammatory factors and urokinase in patients with polycystic kidney stones.…”
Section: Comparison Of Complication Rate and Stone Clearance Ratementioning
confidence: 99%